THE NEGATION OF THE PASSIVE VOICE IN THE PERFECT CONTINUOUS TENSES OF THE ENGLISH LANGUAGE AND THE CROSS-LINGUISTIC PROOF OF ITS NECESSITY BASED ON THE UZBEK ASPECTUAL SYSTEM - Rustamov Saidg‘offorxon Asilbek o‘g‘li (International Journal of Literature and Language Studies, 2026)
This article analyzes the dogma regarding the non-use of the Passive Voice in the Perfect Continuous tenses within English language textbooks. The purpose of the study is to prove the necessity of the '' formula in accurately translating the Uzbek "perfect-continuous passive" (-ib kelinmoqda, -ib kelinayotgan edi) constructions into English. Through corpus analysis and transformation methods, it was determined that traditional alternatives (Simple Perfect Passive or Continuous Passive) lead to a loss of aspectual meaning in translation.